Islamic Talqin in Javanese Community Funeral and Its Relation to Language Socialization: An Ethnolinguistic Research - Gunawan, Sindy Alicia; Qadafi, Ahmad Muammar (Fakultas Ilmu Budaya Universitas Mulawarman, 2025)
Studies on funeral practices among cultures have shown that the practice revolving around death can reveal a lot about the culture. This ethnolinguistic research aims to describe the phenomenon of Islamic talqin as a funeral practice in a Javanese community in Central Kajen, Giri village, Kebomas subdistrict, Gresik city and explore its connection to language socialization. Qualitative strategies involving direct observation and interviews were implemented to conduct this study. In order to describe the funeral practice and investigate its connection to the language socialization of the community, the techniques of analysis used microlevel and macrolevel analysis. The findings show that the talqin practice exhibits the community’s perception about death which experiences gradual change from youth to adults. Moreover, in relation to the language socialization within the community, it is found that the comprehension of Javanese language and Arabic key terms in Islamic teaching relevant to the shared religious identity within the community are deemed as key features to be accepted as a competent member of the community. Keywords: funeral, Javanese community, language socialization, talqin